Analisis Pengarub Syariah Compliance dan Gaji Dengan Komitmen Organisasional Sebagai Variabel Pemoderasi Pada Kinerja Koperasi Syariah di Kabupaten Aceh Tamiang - Musyarrafah Itsnaini; Chuzaimah Batubara; Nurhayati Nurhayati; Sulaiman W (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the effect of Sharia Compliance and compensation on perfomance through organizational commitmen for employees of the sharia cooperative in Aceh Tamiang. This research is quantitative descriptive. The population in this study were all employees of sharia cooperative as many as 42 respondents. Sampling used is purposive sampling with the technique taken is saturated sampling (census). The researcher gave questionnaires to the respondents and processed the data using the SPSS Version 22 application. The analytical method used is Path Analysis. The results showed that the variables of the compensation has no effect on the organizational commitmen, while the variables of sharia compliance has an effect on the organizational commitmen. Compensation variable have no effect on the performance variable. While the variables of Sharia compliance, and organizational commitmen have a positive and significant effect on the performance variable. And the organizational commitmen variable can mediate the two independent variables on the dependent variable, namely the performance variable.